A Semi‐Rationally Engineered Bacterial Pyrrolysyl‐tRNA Synthetase Genetically Encodes Phenyl Azide Chemistry. Issue 3 (11th June 2018) - Fladischer, Patrik; Weingartner, Alexandra; Blamauer, Johannes; Darnhofer, Barbara; Birner‐Gruenberger, Ruth; Kardashliev, Tsvetan; Ruff, Anna Joelle; Schwaneberg, Ulrich; Wiltschi, Birgit
Abstract : The site‐specific incorporation of non‐canonical amino acids (ncAAs) at amber codons requires an aminoacyl‐tRNA synthetase and a cognate amber suppressor tRNA (tRNACUA ). The archaeal tyrosyl‐tRNA synthetase from Methanocaldococcus jannaschii and the pyrrolysyl‐tRNA synthetase (PylRS) from Methanosarcina mazei have been extensively engineered to accept a versatile set of ncAAs. The PylRS/tRNACUA pair from the bacterium Desulfitobacterium hafniense is functional in Escherichia coli, however, variants of this PylRS have not been reported yet. In this study, the authors describe a bacterial PylRS from Desulfitobacterium hafniense, which the authors engineered for the reactive ncAA para ‐azido‐l ‐phenylalanine ( Dh AzFRS) using a semi‐rational approach. Dh AzFRS preferred para ‐azido‐l ‐phenylalanine to the canonicall ‐phenylalanine as the substrate. In addition, the authors demonstrate the functionality in E. coli of a hybrid Dh AzFRS carrying the first 190 N‐terminal amino acids of the Methanosarcina mazei PylRS. These results suggest that bacterial and archaeal PylRSs can be "mixed and matched" to tune their substrate specificity. Abstract : The site‐specific incorporation of non‐canonical amino acids with side chains containing reactive bioorthogonal groups has become a powerful tool for the directed modifications of proteins. Here, the authors engineer the pyrrolysyl‐tRNA synthetase from Desulfitobacterium hafniense for the incorporation of the reactive phenylalanine analog para ‐azido‐l ‐phenylalanine in response to an in‐frame amber codon. The mutant Dh PylRS[N176A/T178G] is a new tool in the toolbox for the modification of proteins with reactive bioorthogonal handles.